From State Paternalism to Neoliberalism in Australian Rural Policy: Perspectives from the Western Australian Wheatbelt - Tonts, Matthew; Jones, Roy (Routledge, 1997)
For much of this century, the rural policies of Australian governments were directed at providing a viable social and economic base for rural communities and country towns. Policies which provided the conditions for stable growth in the agricultural economy, together with equitable levels of access to services such as schools, hospitals and public housing, were seen as instrumental in the development of stable rural communities. More recently, however, the process of global economic restructuring, agricultural adjustment, farm amalgamation and rapid technological change, have contributed to the declining socio‐economic viability of many rural areas. This pattern of decline has been compounded over recent years by the emergence of state and federal government policies based upon the principles of ‘neoliberalism’. The emergence of this approach to rural policy has meant that state and federal governments have, increasingly, withdrawn from effective regional development strategies, rationalised the levels of public service provision, and devolved much of the responsibility for community well‐being to the local level. This paper critically reviews the changing governmental approaches to rural development, and reflects upon some of the outcomes of these policy changes in the wheatbelt of Western Australia.